Current situation and challenges regarding biosimilars in Japan: an example of trastuzumab biosimilars for breast cancer. (11th February 2019) - Hara, Fumikata; Tajima, Kentaro; Tanabe, Kosuke
Biologics have dramatically changed breast cancer treatment, and trastuzumab has been an essential treatment drug for HER2-positive breast cancer. The introduction of trastuzumab biosimilar offers the potential to deliver long-term cost savings plus efficiencies for healthcare systems in Japan. The goal of biosimilar development is to demonstrate comparability to the original biologic with a different development concept from that of the original biologic. Hence, a better understanding of the biosimilar itself is urgently needed for appropriate adoption and the integration of trastuzumab biosimilars into oncology clinical practice by all stakeholders. This article focuses on the current situation of biosimilars and future perspectives in Japan by using the trastuzumab biosimilar as an example.